Psychological and Forensic Challenges Regarding Youth Consumption of Pornography: A Narrative Review - Aina M. Gassó; Anna Bruch-Granados (MDPI AG, 2021)
Nowadays, technology has become part of the daily activities of a large part of the population. Many of the activities and development and socialization processes of minors and young people have been transferred to the online world, generating attention and concern from the educational, scientific, and forensic communities. One of the most worrying issues derived from this new online world is the consumption of pornography by teens. The objective of this literature review is to draw attention to the consequences and emotional disturbances derived from the consumption of pornography in young people, as well as the forensic implications of this phenomenon, among which are paraphilias, perpetration, and victimization of sexual assaults, and the development of new forms of online sexual victimization. The main findings suggest that the first contact with pornography starts at the age of 8 years old, with important behavioral and psychological consequences, such as hypersexualization, emotional disturbances, and the perpetuation of gender inequality. Furthermore, pornography consumption by youth has been linked to the exacerbation of paraphilias, an increase in sexual aggression perpetration and victimization, and, finally, it has been linked to an increase in online sexual victimization. Implications and future lines of research are discussed.